Pharmacist-managed Diabetes Clinic in Malaysia - Does the Number of Follow-up Visits Really Matter? - Abdullah, Mithali Jacqueline; Mei Tew, Mei; Tan, Pei Hoon; Koh, Jing Hui; Md Osman, Nurhayati; Keat Chan, Huan (Journal of Pharmacy Practice and Community Medicine)
Background: The involvement of pharmacists in diabetes education and management has been shown to improve patient outcomes worldwide. The pharmacist-managed Diabetes Medication Therapy Adherence Clinic (DMTAC) has been introduced across public healthcare settings in Malaysia to enhance patient adherence to treatment. Objective: This study was designed to assess the effectiveness of the DMTAC in optimizing the glycemic control of diabetic patients, and to subsequently identify the relationship between the number of follow-up visits and the glycemic control. Method: This was a retrospective cohort study performed in the department of Pharmacy, Sultan Abdul Halim Hospital, Kedah, Malaysia. All the patients, who had type 2 diabetes mellitus, made at least four visits to the pharmacist-managed DMTAC during May 2014 and April 2016, and had their HbA1c levels tested once each before enrolled in the DMTAC and within the same month of the last visit, were included. Percentage of patients achieving the targeted HbA1c level of 7.5% or below, and factors associated with the achievement of the targeted HbA1c level were recorded. Results: Only 21% of patients managed to achieve the targeted HbA1c level. Higher baseline HbA1c (OR: 2.34; 95% CI: 1.14, 4.79) and FPG (OR: 1.41; 95% CI: 1.02, 1.95) levels were more likely to lead to a non-optimized HbA1c level. Conclusion: Despite the effectiveness of the DMTAC in improving the glycemic control, majority of the patients did not achieve targeted level. Number of visits to the DMTAC is not a determinant of the targeted outcome and should not be used as discharging criteria in DMTAC.
Keywords: Pharmacist-managed; Diabetes clinic; HbA1c; Visit; Malaysia